Identifying 'Urban Void' Along the Shortest Path in the University Tramway and Walking Environment - Imen, Hassani (International Journal of Membrane Science and Technology, 2023)
The New City of Ali Mendjli tram line is more than just a public transportation axis; it represents a new tourist product that strongly impacts the socioeconomic environment and the city's image. Since its inauguration in 2014, it has been catering to a student population estimated at 60,000. However, the layout of this dedicated line raises issues concerning the accessibility of the neighborhoods and the buildings it serves. Throughout its 400m corridor, we have identified accessibility constraints stemming from inadequate topography, indirect access to buildings within the central areas, and an unclear urban landscape, unfortunately, unqualified due to the city's design based on a network of vehicular traffic. In this quintessential university town, student housing can present an opportunity for sustainable development, especially when taking advantage of its proximity to the tramway. Therefore, the New City needs to craft a distinctive image worthy of its status and display its local identity. This article aims to identify the tramway as a means of public transportation concerning its practical, comfortable, and secure usage. Additionally, we seek to explore perspectives on optimizing university commuters' movements through walking. To achieve this, we present an experience that analyzes students' perception of their university environment, its strengths, and risks regarding circulation, pathways, and locations through the interpretation of visual diagrams. The conclusions drawn from this exercise will aid in designing "void frameworks" intended as markers to assist pedestrians in orienting themselves from the tramway, ensuring sustainable development for the New City of Ali Mendjli.